Host range evaluation of the leaf-feeding beetle, Zygogramma bicolorata and the stem-boring weevil, Listronotus setosipennis demonstrates their suitability for biological control of the invasive weed, Parthenium hysterophorus in Ethiopia. Issue 3 (4th March 2019) - Mersie, Wondi; Alemayehu, Lidya; Strathie, Lorraine; McConnachie, Andrew; Terefe, Shitaye; Negeri, Mulugeta; Zewdie, Kassahun
ABSTRACT: The invasive weed, parthenium ( Parthenium hysterophorus L.) (Asteraceae: tribe Heliantheae), damages agriculture, adversely impacts biodiversity and is hazardous to human and animal health in Ethiopia. The host range of two natural enemies, a leaf-feeding beetle, Zygogramma bicolorata (Coleoptera: Chrysomelidae) and a stem-boring weevil, Listronotus setosipennis (Coleoptera: Curculionidae) was evaluated for biological control of the weed in Ethiopia. The specificity of Z. bicolorata and L. setosipennis was assessed against 29 and 31 non-target plant species, respectively. The host range of Z. bicolorata and L. setosipennis was first assessed using no-choice tests to examine their oviposition and feeding response on non-target plants. Although oviposition by Z. bicolorata occurred on six non-target species in four Asteraceae species in no-choice tests, it was significantly lower than on parthenium and no larvae developed. Zygogramma bicolorata nibbled the leaves of one of the five niger seed ( Guizotia abyssinica L. – an oil seed crop closely related to parthenium) cultivars tested, but feeding and oviposition were significantly less than on parthenium. Furthermore, choice tests indicated that Z. bicolorata did not oviposit nor feed on G. abyssinica when parthenium was present. In no-choice tests, L. setosipennis did not oviposit on any of the non-target species assessed. Mean oviposition on parthenium was 39.0 ± 3.4 eggs per plant whereas no eggs were laid on any of the 31 species tested. Based on these and other host range tests, permission was obtained to field release Z. bicolorata and L. setosipennis in Ethiopia.